Progress in microalgae cultivation photobioreactors and applications in wastewater treatment: A review - Ting, Han; Haifeng, Lu; Shanshan, Ma; Zhang, Yuanhui; Zhidan, Liu; Na, Duan (International Journal of Agricultural and Biological Engineering, 2017)
Using microalgae to treat wastewater has received growing attention in the world because it is regarded as a novel means for wastewater treatment. It is commonly recognized that large-scale cultivation and commercial application of microalgae are limited by the development of photobioreactor (PBR). Although there are a lot of PBRs for microalgae pure cultivation which used culture medium, specialized PBRs designed for wastewater treatment are rare. The composition of wastewater is quite complicated; this might cause a very different photosynthetic effect of microalgae compared to those grown in a pure cultivation medium. Therefore, PBRs for wastewater treatment need to be redesigned and improved based on the existing PBRs that are used for microalgae pure cultivation. In this review, different PBRs for microalgae cultivation and wastewater treatment are summarized. PBR configurations, PBR design parameters and types of wastewater are presented. In addition, the wastewater treatment efficiency and biomass productivity were also compared among each type of PBRs. Moreover, some other promising PBRs are introduced in this review, and a two-stage cultivation mode which combines both closed and open system is discussed as well. Ultimately, this article focuses on current problems and gives an outlook for this field, aiming at providing a primary reference for microalgae cultivation by using wastewater.Keywords: microalgae cultivation, wastewater treatment, photobioreactor (PBR), reviewDOI: 10.3965/j.ijabe.20171001.2705Citation: Han T, Lu H F, Ma S S, Zhang Y H, Liu Z D, Duan N. Progress in microalgae cultivation photobioreactors and applications in wastewater treatment: A review. Int J Agric & Biol Eng, 2017; 10(1): 1–29.